GENETIC DIVERSITY OF FISH (MUGIL CEPHALUS L.) IN VIETNAM USING SSR MARKERS - Viet Thanh, Tran Thi; Long, Phan Ke; Durand, Jean Dominique; Phong, Dinh Thi (Vietnam Journal of Biotechnology, 2018)
The flathead grey mullet species (Mugil cephalus L.) Vietnam is an euryhaline fish whose distribution ranges from the North to the South. Currently, M. cephalus is facing the threat of overexploitation, and the number of individuals in most populations is declining fast. In order to conserve the species in Vietnam, it is necessary to evaluate its genetic diversity. Therefore, this study was carried out in Vietnam from August 2012 to June 2015. The results of our study provided the analysis for 12 locus microsatellites (SSR) from 70 mature individuals (standard length > 25 cm). The study also identified a total of 35 alleles for all loci studied, among which 10 loci were polymorphic. Average value of polymorphic information content (PIC) for each polymorphic marker was 0.2889 (0.0289 to 0.5918). Coefficient heterozygous gene Ho = 0.942; He = 0.517; Fst = 0.216; Fis = - 0.8211 (Fis < 0). The genetic relationship of 70 specimens or M. cephalus in Vietnam were divided in three main groups according to three specific geographic distributions in the country, the Gulf of Tonkin, the Central and the South. There were also mixed clusters observed among the three studied regions. Individuals in close geographical distance often clustered together and formed separate groups, in which the level of molecular changes were quite low, 29% among populations, and 71% among individuals within the same population.